Superior ophthalmic vein thrombosis following coil embolization of posterior communicating artery aneurysm: Report of two cases. Issue 1 (January 2022) - Abri Aghdam, Kaveh; Nilforushan, Naveed; Zand, Amin; Kohansal, Rahim
Introduction: The purpose was to present two patients with superior ophthalmic vein thrombosis following coil embolization of posterior communicating artery aneurysm, that have not been reported after this particular procedure yet. Methods: We present two patients with subarachnoid hemorrhage due to posterior communicating artery aneurysms, who were treated with stent-assisted coil embolization. Shortly after the procedure, both cases demonstrated painful proptosis, ophthalmoplegia, increased intraocular pressure, intraretinal hemorrhage and macular edema on the ipsilateral side, with congestion of intraorbital tissues and thickened and dilated superior ophthalmic vein in neuroimaging investigation. The occlusion was confirmed by digital subtraction angiography. Results: Patients were treated with anticoagulant agents and systemic corticosteroids immediately and then received medical treatment by an ophthalmologist for ocular complications of superior ophthalmic vein thrombosis. Conclusion: Isolated superior ophthalmic vein thrombosis (SOVT) is rare, but may be associated with sight-threatening complications. After intracranial interventions on cerebral vessels, clinical features of SOVT including choroidal effusion syndrome should be investigated, and the patients should receive prompt and proper care including ophthalmic medications and systemic anticoagulants to restrict the ocular and systemic complications.